Amyloid-Related Imaging Abnormalities in Anti-Amyloid Monoclonal Antibody Therapy for Alzheimer’s Disease: Expert Recommendation for Standard MRI Protocol - Jimin Kim; Eunhee Kim; Mina Park; Yun Jung Bae; Chong Hyun Suh; Sung-Hye You; Younghee Yim; Ho-Joon Lee; Jin Wook Choi; Se Won Oh; Won-Jin Moon (Journal of the Korean Society of Radiology)
The introduction of anti-amyloid therapies for Alzheimer’s disease (AD), such as lecanemab (Lequembi ®), which was recently approved in Korea, necessitates careful monitoring for amyloid-related imaging abnormalities (ARIA) using brain MRI. To optimize ARIA monitoring in Korean clinical settings, the Korean Society of Neuroradiology (KSNR) and the Age and Neurodegeneration Imaging (ANDI) Study Group proposed MRI protocol recommendations on essential MR sequences, MRI acquisition parameters, timing and condition of MRI examinations, and essential details to provide a scientific basis for maximizing the safety and efficacy of AD treatment. A customized, standardized MRI protocol focusing on Korea’s healthcare environment can improve ARIA management and ensure patient safety through early detection of potential anti-amyloid therapy side effects, thereby enhancing treatment quality.